Antihypertensive Treatment in the Elderly and Very Elderly: Always "the Lower, the Better?". (22nd September 2011) - Mazza, Alberto; Ramazzina, Emilio; Cuppini, Stefano; Armigliato, Michela; Schiavon, Laura; Rossetti, Ciro; Marzolo, Marco; Santoro, Giancarlo; Ravenni, Roberta; Zuin, Marco; Zorzan, Sara; Rubello, Domenico; et al.
Abstract : Arterial hypertension (HT) is age dependent and, with the prolongation of life expectancy, affects more and more elderly people. In the elderly, HT is a risk factor for organ damage and cardiovascular (CV) events. Both pharmacologic and nonpharmacologic reduction of blood pressure (BP) is associated with a corresponding decrease in systolic-diastolic or isolated systolic HT. Clinical trials have shown that BP lowering is associated with a decrease in stroke and other CV events. Therefore, BP reduction per se appears more important than a particular class of antihypertensive drugs. The benefit of antihypertensive treatment has been confirmed up to the age of 80 years, remaining unclear in the octogenarians. The benefit in lowering diastolic BP between 80 and 90 mmHg is well established, while that of lowering systolic BP below 140 mmHg requires further confirmations.